Peran Orang Tua Dalam Mengenalkan Pendidikan Seks Pada Anak Di Tk Tunas Rimba Kota Salatiga - Fitri Kurniawati; Ajeng Ayu Widiastuti (PAUDIA : Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2022)
AbstractThe purpose of this study was to determine the role of parents in introducing sex education to children and to determine the supporting and inhibiting factors of the role of parents in introducing sex education. This research is a qualitative descriptive study. This study focuses on the role of parents in introducing early sex education. Data collection techniques used were questionnaires, observations and interviews to find out how far and how the role of parents in introducing sex education to children as well as supporting and inhibiting factors in the introduction of sex education in children. The subjects in this study were seven (7) parents. The results of the study indicate that the role of parents in introducing sex education to children has been carried out by parents although it has not been maximized. The role that parents have done is to give an example of loving the body, supervising children when watching television, supervising children when playing gadgets (youtube). While the things that have not been done by parents are teaching not to undress in front of the opposite sex, providing clothes according to the child's gender, giving examples of protecting themselves from sexual violence, mentioning the name of the child's genitals properly, separating the child's bedroom according to gender, separating the bedroom sleeping with their parents, and teaching the etiquette of asking permission to enter the parents' room. The factors supporting and inhibiting the role of parents in introducing sex education for children are Gadgets, Family, Communication between parents, Culture, Knowledge and Methods of Delivery of Parents.Keywords: Parental Role, Parental Involvement, Sex Education for AUD, Child Education, Support System AbstrakTujuan dalam penelitian ini untuk mengetahui peran orangtua dalam mengenalkan pendidikan seks, faktor pendukung dan penghambat peran orangtua dalam mengenalkan pendidikan seks untuk anak. Penelitian ini merupakan penelitian deskriptif kualitatif. Penelitian ini memfokuskan pada peran orangtua dalam mengenalkan pendidikan seks usia dini. Teknik pengumpulan data yang digunakan adalah kuesioner (angket), observasi dan wawancara untuk mengetahui seberapa jauh dan bagaimana peran orangtua dalam mengenalkan pendidikan seks pada anak serta faktor pendukung dan penghambat dalam pengenalan Pendidikan seks pada anak. Subyek dalam penelitian ini sebanyak tujuh (7) orangtua. Hasil penelitian menunjukkan bahwa peran orangtua dalam mengenalkan pendidikan seks pada anak sudah dilakukan oleh orangtua walaupun belum maksimal. Peran yang telah dilakukan orangtua ialah memberi contoh menyayangi tubuh, mengawasi anak ketika menonton televisi, mengawasi anak ketika bermain gadget (youtube). Sedangkan hal yang belum dilakukan oleh orangtua ialah mengajarkan tidak membuka baju di depan lawan jenisnya, menyediakan pakaian sesuai jenis kelamin anak, memberikan contoh melindungi diri dari kekerasan seksual, menyebutkan nama alat kelamin anak dengan semestinya, memisahkan kamar tidur anak sesuai jenis kelaminnya, memisahkan kamar tidur anak dengan orangtua, dan mengajarkan etika meminta izin masuk ke kamar orangtua. Adapun faktor pendukung dan penghambat peran orangtua dalam mengenalkan pendidikan seks untuk anak ialah Gadget, Keluarga, Komunikasi antar orangtua, Budaya, Pengetahuan dan Cara Penyampaian orangtua.  Kata kunci: Peran Orangtua, Keterlibatan Orangtua, Pendidikan seks bagi AUD, Pendidikan Anak, Support System